Imaging inflammation and its resolution in health and disease: current status, clinical needs, challenges, and opportunities. Issue 12 (9th October 2019) - Liu, Christina H.; Abrams, Natalie D.; Carrick, Danielle M.; Chander, Preethi; Dwyer, Johanna; Hamlet, Michelle R. J.; Kindzelski, Andrei L.; PrabhuDas, Mercy; Tsai, Shang‐Yi Anne; Vedamony, Merriline M.; Wang, Chiayeng; Tandon, Pushpa
Abstract : Inflammation is a normal process in our body; acute inflammation acts to suppress infections and support wound healing. Chronic inflammation likely leads to a wide range of diseases, including cancer. Tools to locate and monitor inflammation are critical for developing effective interventions to arrest inflammation and promote its resolution. To identify current clinical needs, challenges, and opportunities in advancing imaging‐based evaluations of inflammatory status in patients, the U.S. National Institutes of Health convened a workshop on imaging inflammation and its resolution in health and disease. Clinical speakers described their needs for image‐based capabilities that could help determine the extent of inflammatory conditions in patients to guide treatment planning and undertake necessary interventions. The imaging speakers showcased the state‐of‐the‐art in vivo imaging techniques for detecting inflammation in different disease areas. Many imaging capabilities developed for 1 organ or disease can be adapted for other diseases and organs, whereas some have promise for clinical utility within the next 5–10 yr. Several speakers demonstrated that multimodal imaging measurements integrated with serum‐based measures could improve in robustness for clinical utility. All speakers agreed that multiple inflammatory measures should be acquired longitudinally to comprehend the dynamics of unresolved inflammation that leads to disease development. They also agreed that the best strategies for accelerating clinical translation of imaging inflammation capabilities are through integration between new imaging techniques and biofluid‐based biomarkers of inflammation as well as already established imaging measurements.—Liu, C. H., Abrams, N. D., Carrick, D. M., Chander, P., Dwyer, J., Hamlet, M. R. J., Kindzelski, A. L., PrabhuDas, M., Tsai, S.‐Y. A., Vedamony, M. M., Wang, C., Tandon, P. Imaging inflammation and its resolution in health and disease: current status, clinical needs, challenges, and opportunities. FASEB J. 33, 13085–13097 (2019). www.fasebj.org